Systematic Error in Respiratory Impedance Using Commercial Equipment Calibrated according to the Manufacturer’s Instructions - Sly, Peter D.; Shackleton, Claire; Czovek, Dorottya; Hantos, Zoltan (American journal of respiratory and critical care medicine, 2018)
To the Editor: Measuring lung function in subjects who find the forced expiratory maneuvers required for spirometry difficult, such as preschool-aged children and elderly patients with chronic obstruction pulmonary disease (COPD), is challenging. Lung function testing in preschool-aged children with cystic fibrosis in the clinical setting. An official American Thoracic Society workshop report: optimal lung function tests for monitoring cystic fibrosis, bronchopulmonary dysplasia, and recurrent wheezing in children less than 6 years of age.